(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2001)
This paper first summarises the idea of the evolution and redefinition of the subject under the other’s eye, very briefly in Parker’s theory for the ’Cambrian Explosion’ and, at greater length, in Levinas’ encounter with the other’s ’face’. It then explores some of the implications of Levinas’ philosophy for the practice of psychotherapy. It concludes that Levinas’ conception of the ’asymmetrical face-to-face’ relationship cannot form the foundation of an ethical therapeutic practice, without either being seriously compromised.